Tourism and wellbeing. (September 2017) - Kay Smith, Melanie; Diekmann, Anya
Highlights: Wellbeing-enhancing tourism is based on a hedonic and eudaimonic spectrum. Eudaimonic tourism activities create more long-term transformational benefits. Optimum tourist wellbeing combines hedonic, altruistic and meaningful experiences. Self-development and existential authenticity form part of tourist wellbeing. Destination planners need to adopt a utilitarian approach to wellbeing. Abstract: Wellbeing has been a philosophical and sociological concern since the beginning of time, and research has extended over time to disciplines such as psychology, health sciences and economics to name just a few. Tourism studies has also become more focused on wellbeing in the last few decades, both from a theoretical and methodological perspective. After examining the philosophical background of wellbeing from different perspectives, the paper takes a closer look at how these frameworks can inform tourism research and practices. It explores the relationship between diverse terminologies and perspectives as well as the ways in which hedonic and eudaimonic wellbeing can be derived through tourism experiences. A spectrum and a model are proposed which outline the relationship between various types of wellbeing, tourism and activities.